Pelatihan Aplikasi Publish or Perish (Pop) pada Mahasiswa Jurusan Akuntansi Syariah - Thalib, Mohamad Anwar (Jurnal Pemberdayaan Umat, 2024)
Purpose: This community service aims to enhance the understanding of Sharia Accounting department students about using the Publish or Perish reference search application. Methodology/approach: This community service is conducted offline, with 23 participants consisting of fifth-semester Sharia Accounting students currently taking the Research Methodology course. Results/findings: The training results indicate an improvement in Sharia Accounting department students' understanding of using the PoP application. Furthermore, the participants understood how to store metadata from Mendeley or Zotero's PoP reference search application. This is evidenced by data from 23 training participants, with 13 participants stating they already understand and 5 participants stating they understand very well. Furthermore, based on the evaluation of participant worksheets, it is evident that participants have been able to find relevant previous research for their thesis proposals. Limitation: This is in line with questionnaire data where 12 participants answered that they understand, seven answered that they understand very well, three answered that they understand less, and one did not understand. Contribution: This training provides an academic contribution by providing references related to PoP training. The practical contribution of this training is that it makes it easier for students to find references in accordance with their research plans. Researchers limited this training to searching for PoP references via the Google Scholar feature.